Program Pengembangan Kemampuan Literasi Dasar Anak Usia Dini Melalui Media Cergam Digital - Amalia Fajriyyatin Najichah (Indonesian Journal of Education and Learning, 2024)
The phenomenon of low literacy in Indonesian society in the current digital era raises various assumptions regarding the causal factors and solutions. Various literature states that this stems from literacy habits from an early age. Related to this problem, there is one innovation in language learning for early childhood. The innovation is expressed in the form of a program to develop basic literacy skills in early childhood through digital illustrated stories. This research aims to find out in depth about the program. Thus, the appropriate method to use in this research is a case study. The subjects in this study were teachers and 25 students from Group B of Marsudi Rini Kindergarten, Karanganyar District, Demak Regency. Research data were obtained through observation, interviews, and documentation. The results of this study show that: (1) the basic literacy development program at Marsudi Rini Kindergarten is carried out with systematic stages with support from inside and outside the school, (2) the basic literacy development program at Marsudi Rini Kindergarten is implemented in an integrated manner with language learning, both receptive and expressive; (3) digital illustrated stories media used in the program is adjusted to the criteria for early childhood development, both in terms of presentation form, content, and language.